Correction: Highly photoluminescent copper carbene complexes based on prompt rather than delayed fluorescence. Issue 29 (28th March 2018) - Romanov, Alexander S.; Di, Dawei; Yang, Le; Fernandez-Cestau, Julio; Becker, Ciaran R.; James, Charlotte E.; Zhu, Bonan; Linnolahti, Mikko; Credgington, Dan; Bochmann, Manfred
Abstract : Correction for 'Highly photoluminescent copper carbene complexes based on prompt rather than delayed fluorescence' by Alexander S. Romanov et al., Chem. Commun., 2016, 52, 6379–6382.